Editorial - Kögler, Patricia (Journal of Hellenistic Pottery and Material Culture, 2021)
Ever since spring 2020 our life has changed, getting more problematic and complicated. The necessary measurements taken to combat the covid-19 pandemic have caused several changes with regard to our professional archaeological work schedule and impeded our research. Excavation campaigns had to be cancelled or could take place only with a drastically reduced team. Conferences and lectures had to be cancelled, postponed or presented online without personal contacts. Specialised libraries had to be closed, and to this day are not fully accessible. University teaching had to be restricted or cancelled. These measurements implied a serious setback for research or at least a slowdown, and impaired publications in print media and publishing houses.